Development and optimization of N‐acetylneuraminic acid biosensors in Bacillus subtilis. (22nd May 2020) - Zhang, Xiaolong; Cao, Yanting; Liu, Yanfeng; Liu, Long; Li, Jianghua; Du, Guocheng; Chen, Jian
Abstract: Transcriptional factor (TF)‐based metabolite‐responsive biosensors are important tools for screening engineered enzymes with desired properties and for the dynamic regulation of biosynthetic pathways. However, TF‐based biosensor construction is often constrained by undesired effects of TF‐binding site sequence insertion on gene expression and unpredictable optimal TF expression levels. In the present study, a stepwise TF‐based biosensor construction approach was developed using an N‐acetylneuraminic acid (NeuAc) biosensor for Bacillus subtilis, as a case study. Specifically, 12 promoters with various strengths were selected as the first promoter library. Next, binding site sequences for the NanR were inserted into various positions of the selected promoter sequences to develop the second promoter library, resulting in 6 engineered promoters containing TF‐binding site sequences (NanO), without major effects on promoter strength. NanR expression cassettes with different expression levels were further integrated to construct the biosensor library, yielding 9 NeuAc biosensors with efficient repression in the absence of NeuAc. Finally, biosensor activation was characterized by testing fold changes in expression levels of the green fluorescent protein reporter in the presence of NeuAc in vivo, which revealed 61‐fold activation when NeuAc was present. The NeuAc biosensor developed in this study can be used for screening engineered enzymes for enhanced NeuAc biosynthesis in B. subtilis . Abstract : The reconstruction and optimization of NeuAc biosensor in Bacillus subtilis .